2017
DOI: 10.1038/s41598-017-17222-3
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortical activity changes during neuroprosthetic-controlled object interaction

Abstract: Brain-computer interface (BCI) controlled prosthetic arms are being developed to restore function to people with upper-limb paralysis. This work provides an opportunity to analyze human cortical activity during complex tasks. Previously we observed that BCI control became more difficult during interactions with objects, although we did not quantify the neural origins of this phenomena. Here, we investigated how motor cortical activity changed in the presence of an object independently of the kinematics that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…This is an important step towards neural speech prostheses for speech impaired users. While our study uses overtly produced speech in non-paralyzed subjects, recent studis show analogous results for paralyzed patients [54,55,56,57], as well as for speech decoding [58], providing reason to believe that similiar results might also be achievable for mute users.…”
Section: Discussionsupporting
confidence: 52%
“…This is an important step towards neural speech prostheses for speech impaired users. While our study uses overtly produced speech in non-paralyzed subjects, recent studis show analogous results for paralyzed patients [54,55,56,57], as well as for speech decoding [58], providing reason to believe that similiar results might also be achievable for mute users.…”
Section: Discussionsupporting
confidence: 52%
“…Consistent with this recommendation, the Cursor Position Subtraction operation was not used in our recent study in which the ReFIT decoder enabled people with paralysis to type using a virtual keyboard 2 . These results add to an emerging story that the effects of some forms of visual feedback on motor cortical activity may be less problematic for BMI decoding than originally predicted 27 (but see 34 , which reports that seeing a BMI arm approaching a graspable object strongly modulates activity).…”
Section: Discussionmentioning
confidence: 50%
“…Although we showed here that visually monitored BMI effector positional effects are minimal and can be ignored during decoding, it is unknown whether more anthropomorphic BMI effectors such as robotic arms 34,37 will induce stronger motor cortical modulation related to effector state (e.g., arm position or joints conformation). This might be expected because these prostheses more directly tap into the sensorimotor system’s native arm-monitoring machinery.…”
Section: Discussionmentioning
confidence: 77%
“…Recently our lab and others have shown that context can modulate the primary motor cortex (M1) (Downey et al 2017, Marsh et al 2015, Ramakrishnan et al 2017, Ramkumar et al 2016. For instance, it has become clear that a reward signal exists in the primary motor cortex (M1), and primary somatosensory cortex (S1) as well (McNiel et al 2016a, McNiel et al 2016b.…”
Section: Introductionmentioning
confidence: 99%